Vasomotor dysfunction in human subcutaneous arteries exposed ex vivo to food-grade titanium dioxide. (October 2018) - Jensen, Ditte Marie; Skovsted, Gry Freja; Lykkesfeldt, Jens; Dreier, Rasmus; Berg, Jais Oliver; Jeppesen, Jørgen Lykke; Sheykhzade, Majid; Loft, Steffen; Møller, Peter
Abstract: Animal studies have shown that titanium dioxide (TiO2 ) exposure affects arterial vasomotor function, whereas little is known about the effects in arteries from humans. This study investigated vasomotor responses after direct exposure of human subcutaneous arteries to food-grade TiO2 (E171) (14 or 140 μg/ml) for 30 min and 18 h. Vasomotor responses to bradykinin, 5-hydroxytryptamine (5-HT), sarafotoxin 6c (S6c) and nitroglycerin were recorded in wire-myographs. Vasoconstrictor responses to 5-HT were increased in arteries exposed to E171 for 18 h ( P  < 0.05). Furthermore, an increase in S6c responses was seen in low concentration E171 exposed arteries (30 min exposure; P  < 0.05). The vasorelaxation response to nitroglycerin was increased in low concentration E171 exposed arteries (30 min exposure; P  < 0.05). Vasorelaxation responses to bradykinin were unaffected after treatment with E171. There was no difference in gene expression levels of intercellular cell adhesion molecule 1, vascular cell adhesion molecule 1, 5-hydroxytryptamine receptor 1B, 5-hydroxytryptamine receptor 2A, endothelin receptor A and endothelin receptor B in E171 exposed arteries after exposure to TiO2 for 30 min or 18 h. In conclusion, this study shows that the same type of vasomotor dysfunction is found in artery segments of rats and humans following ex vivo exposure to E171. Highlights: Exposure of human arteries to E171 resulted in increased vasocontraction response. There were unaltered expressions of 5-hydroxytryptamine or sarafotoxin 6c receptors. The exposure did not change the expression of cell adhesion molecules in arteries. Exposure to E171 increased the endothelial-independent vasorelaxation response.